Finite Element Analysis Of Bridge Girder Retrofitted By A Post-Tensioned Technique - Malek, Siti Norshafiqah Aini Abd (Universiti Sains Malaysia, 2021)
The rapid development of multi-span simply supported bridges is built as transportation infrastructure and the increasing number of box girder bridges widely utilized as important components of the structure. As a service structure, the bridge is always prone to the problem of deterioration and damages as consequence, they indicate insufficient performance, in terms of durability, functionality, and safety. This study aims to determine the failure of structure and retrofit the segmental box girder bridge by using the post-tension technique and analyze the segmental box girder bridge using the finite element software. The segmental span bridge with a length of 30 meters is modeled. The uniform distributed load of 350 kN/m and the gravity load as the self-weight of the structure is applied on the bridge. The assessment of the bridge structure condition was carried out to analyze the displacement, deflection, stress, and strain of the bridge structure. The Post-tension technique of retrofitting is used to reduce the failure of the bridge and increase the strengthening of the bridge. The tendon length of 12 meters is used as the post-tension reinforcement. The result of the study and methodology will be presented and discussed in improving the structure in terms of enhancing the quality of the bridge. The results of the developed models were in good correlation with the experimental results of the model were evaluated.